Pharmacy education in India and its neighbouring countries - Sachan, Ayushy; Sachan, Anupam K; Gangwar, Sudhir S (International Current Pharmaceutical Journal, 2012)
During the past few years, the pharmacy profession has expanded significantly in terms of professional services delivery and now has been recognized as an important profession in the multidisciplinary provision of health care. The Pharmacist is a key component of healthcare and manages the human resource to support the growth. In contrast to the situation in developed countries, pharmacists in developing countries are still underutilized and their role as health care professionals is not deemed important by either the community or other health care providers. The aim of this paper is to highlight the role of pharmacists in developing countries, particularly in India, Pakistan and Bangladesh. The paper draws on the literature related to the pharmacy profession in the country in the context of the current directions of health care. The paper highlights the current scenario and portrays the pharmacy profession in India, Bangladesh and Pakistan. It concludes that although the pharmacy profession in developing countries is continuously evolving, the health care system which yet to recognize the pharmacist's role. This lack of recognition is due to the limited interaction of pharmacists with the public. Pharmacists in developing countries are concerned about their present professional role in the health care system. The information presented in this paper may stimulate discussion and critical analysis and planning, and will be of value in further adaptation of the pharmacy education to desired educational outcomes. These are times of enormous change in healthcare and the pharmacy profession and pharmaceutical education must prepare students to enter into the practice of pharmacy. DOI: http://dx.doi.org/10.3329/icpj.v1i9.11622 International Current Pharmaceutical Journal 2012, 1(9): 294-301